Stimuli‐Responsive Sponge for Imaging and Measuring Weak Compression Stresses. Issue 3 (11th December 2022) - Ono, Nahoko; Seishima, Ryo; Okabayashi, Koji; Imai, Hiroaki; Fujii, Syuji; Oaki, Yuya
Abstract: Imaging and measuring compression stresses secure a safe and healthy life. Compression stresses in kPa range are not easily detected by conventional mechanoresponsive materials because microscopic molecular motion of the chromophores is not induced by such weak stresses. Moreover, imaging of the stress distribution is not achieved so far. The present study shows a sponge device combining two stimuli‐responsive materials, a capsule releasing interior liquid and color‐changing polymer in responses to compression stress and chemical stimulus, respectively. The stimuli‐responsive capsule is dispersed on a melamine sponge comprised of the fibers with coating the layered polydiacetylene (PDA). The application of weak compression stresses induces collapse of the capsules, outflow of the interior liquid, and subsequent irreversible color change of PDA. The cascading response in the sponge device colorimetrically enables imaging of the distribution and measuring the strength of the compression stresses in kPa range. Furthermore, the device demonstrates imaging and measuring unknown weak compression stresses applied by the irregular‐shaped objects. A couple of clinical issues in surgical operation of intestine are studied using the stress‐imaging sponge device. The device and its design strategy can be applied to stress imaging in a variety of fields. Abstract : Imaging invisible force distribution is a significant challenge in chemistry and materials science. The present work shows stimuli‐responsive sponge device for imaging and measuring weak compression stresses in kPa range and mm scale. The device visualizes and quantifies the local compression stress and its distribution applied by irregularly shaped objects, such as plastic ornaments and surgical devices.